PENERAPAN MODEL PEMBELAJARAN REACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERRING) DISERTAI MEDIA FOTO KEJADIAN NYATA DALAM PEMBELAJARAN FISIKA DI SMAN 1 PAKUSARI - Hilya Wildana Sofia; Sutarto Sutarto; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2017)
This experimental research related on the implementation of REACT (Relating,Experiencing, Applying, Cooperating, Transferring) learning model with realphenomenon photo media in learning physic at SMA Negeri 1 Pakusari in2016/2017 academic year. The objectives of this research were to describe thestudent’s learning activities and to study the effect of the model to the physiclearning achievment. The design of this research was post test only control groupdesign. The technique of data collection on this research were test, observation,documentation and interview. The student’s learning activity data was collected byobservation sheet and analyzed descriptively. The learning achievment data wascollected by using post test and analyzed by using Independent Sample t test onSPSS 22. Finding of the research were (1)the average of student’s learning activityuusing REACT learning model with real phenomenon photo media was 89,4% whichmeans active; (2) the difference between experiment class and control class is doneby obtained significant value (2-tailed) of 0.000 ≤ 0.05. It means the result of thisresearch proved that the use of REACT learning model with real phenomenon photomedia significantly affected the cognitive learning outcomes at tenth grade SMANegeri 1 Pakusari.Keywords: REACT learning model, real phenomenon photo media, learningachievement , learning activities